Athletes’ psycho-physical training and cognitive restructuring module to enhance university-athlete students’ well-being - Motevalli, Saeid; Sulaiman, Tajularipin; Kai, Yan Wong; Wan Jaafar, Wan Marzuki (Bentham Open Publisher, 2022)
Many health practices demonstrate that some integrative approaches could be beneficial in fostering self-care and well-being for a healthy lifestyle. Athletes are exposed to elevated rates of stress and low control of performance during the competition, which puts them at increased risk for a range of mental health problems and poor well-being. Despite the psychological risks associated with their competitive circumstances, limited attention has been given to identifying the psycho-physical and cognitive strategies contributing to the well being of university athletes’ The integration of psycho-physical and cognitive restructuring may be an effective technique for increasing the well being and performance of university athletes’ . Therefore, in this module, the researchers have included numerous elements related to physical training, psychological training and cognitive restructuring in order to improve university student-athlete to further construct positive self-esteem, confidence, expectations, good performance and also enhance monitoring and control over the internal and external environment in which lead to having a beneficial influence on anxiety, stress or tension that may experience in an extreme situation such as a sports competition. We discuss the benefits of this module and provide practical strategies and techniques to implement for sports psychologists, counselors, and educational authorities. This module urges university athletes to create mental health, well-being awareness and early cognitive prevention strategies to improve the educational environment and contribute to the athletes’ performance.